NURSING RESEARCH: RECOGNIZING THE STATUS AT ONE PUBLIC UNIVERSITIES - Aida Maria Peres (Universidade Federal do Paraná, 2001)
The need to deepen the understanding about the several relations that go through the nursing research has motivated the creation of this work. Aiming at recognizing the status of the nursing research at public universities, we have worked with the approach of the General Sistems Theory (Bertalanffy, 1977) to build the context from the multiplicity of available information. The qualitative approach has allowed the observation and understanding how each researcher and his/her institution live reality. To gather data, recorded interviews were carried out with researchers of the Nursing Department of the Federal University of Paraná and representatives of the teaching and research at the university and in the Health Sciences Sector. The interviews have given detailed answers, regarding the needs, the dificulties and easiness that the researchers met related to the research's several steps, including issues about information sources and fomentation. Many expectations and needs were identified related to the subject, making the acknowledgement of the contextualized situation easier, able to cause changes.